2017
DOI: 10.1111/1750-3841.13674
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Nutrition and Health Deficiencies in Older Adults: A Role for Food Innovation?

Abstract: The aim of this review is to describe the factors contributing to diminished food intake, resulting in nutritional deficiencies and associated health conditions in older adults and proposes food innovation strategies to mitigate these. Research has provided convincing evidence of a link between healthy eating patterns and healthy aging. There is a need to target new food product development (NPD) with functional health benefits specifically designed to address the particular food-related needs of older consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 95 publications
0
53
0
Order By: Relevance
“…We recommend carrying out assessments for dysphagia in all patients at risk of malnutrition. The assessment should be carried out because patients at risk of malnutrition and dysphagia often have different diets or meal consistency requirements (Baugreet, Hamill, Kerry, & McCarthy, ; Brown, Ross, Jones, Hughes, & Banks, ; Laguna et al, ). This recommendation is supported by the findings of Popman, Richter, Allen, and Wham (), who described an association between a high risk of malnutrition and a higher prevalence of dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…We recommend carrying out assessments for dysphagia in all patients at risk of malnutrition. The assessment should be carried out because patients at risk of malnutrition and dysphagia often have different diets or meal consistency requirements (Baugreet, Hamill, Kerry, & McCarthy, ; Brown, Ross, Jones, Hughes, & Banks, ; Laguna et al, ). This recommendation is supported by the findings of Popman, Richter, Allen, and Wham (), who described an association between a high risk of malnutrition and a higher prevalence of dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…The link between adequate nutrient intake, both of macronutrients and micronutrients, and healthy ageing is increasingly supported by the scientific literature [9]. A study on European population groups (aged 64 or over) indicated that 11% fell below the reference nutrition intake (RNI) for at least one of the following nutrients: zinc, vitamins B12 and C, whilst in 21%, intakes of vitamin D, folic acid, calcium, selenium and iodine were below the RNI [10].…”
Section: Ageingmentioning
confidence: 99%
“…Roininen et al () showed that older adults preferred foods that can be consumed effortlessly providing an easy eating experience, but at the same time, textures that were too smooth or too soft were not appreciated. Furthermore, chemosensory acuity is negatively affected by factors such as dentures which is associated with the ageing process and this has been shown to lead to negative changes in food appreciation and diet (Baugreet et al , ). This vulnerable group of elderly consumers demand nutrient dense foods with the precise sensory attributes to improve food intake and digestion hence the need for research in this area.…”
Section: Introductionmentioning
confidence: 99%